Relationship between the Twin Deficit Hypothesis and the Inflation: Case of Turkey (2010-2019) - Burhan DOGAN; Burak SAYKAL (The Institute of Academic Research and Publication (IARP), 2022)
Twin deficit hypothesis; It emerges when budget deficits and current account deficits are observed simultaneously. Exchange rate fluctuations have an impact on both cost inflation and consumer inflation through production costs due to Turkey's import substitution mode of production. In this study, the relationship between the twin deficit hypothesis and consumer inflation was analyzed using VAR analysis and Granger causality tests using quarterly data between the periods 2010: Q1 and 2019: Q4. According to the results obtained; while the twin deficit hypothesis was not supported in Turkey in the period discussed, it was observed that the budget deficit and current account deficit increased inflation.